FAMILY CONFLICT AMONG FORMER DRUG ADDICTS : AN EMPIRICAL STUDY - Fauziah, Ibrahim; Ezarina, Zakaria; Norulhuda, Sarnon; Salina, Nen; Tharshini, N. K. (JPSP publishes, 2022)
Up until now, not many studies have been done to identify family conflict that occurs among former drug addicts in the rehabilitation period. If not being handled properly, this factor may lead to an increase in the drug relapse rate among former drug addicts. Therefore, this study is conducted to (1) identify the level of family conflict among former drug addicts during the rehabilitation period, and to (2) identify factors that influence family conflict among former drug addicts. This study was performed using a quantitative cross-sectional survey design. A total of 380 former drug addicts who have completed their rehabilitation program at the Cure and Care Rehabilitation Centre (CCRC) were chosen as the respondents of the study. The collected data were analysed using descriptive and inferential statistics. The results of the study found that the level of family conflict among former drug addicts is only at a moderate level. Analysis of the study shows that their desire for drugs and the combination of emotional disturbance, social surrounding stress, and self-efficacy to avoid drugs are factors that contribute to family conflict among former drug addicts. This study gives implications on the need to enhance policies related to drug treatment programs and conflict resolutions towards relapse prevention.